2022
DOI: 10.3390/plants11101293
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Genotoxic Evaluation of Biosynthesized Silver Nanoparticles Using Moringa oleifera on MCF-7 and HUVEC Cell Lines

Abstract: Nowadays, green synthesized nanoparticles (NPs) are extensively investigated to explore their biological potential. They are being explored to treat different infectious and cancerous diseases. Therefore, the current study was designed to evaluate the cytotoxic and genotoxic effects of biosynthesized silver nanoparticles (AgNPs) from the medicinal plant Moringa oleifera on breast cancer (MCF-7) and HUVEC (human umbilical vein endothelial cells) cell lines. M. oleifera-mediated AgNPs were synthesized from the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…On the other hand, the presence of Bisdemethoxyrcurcumin exclusively in the ethanolic fraction suggests the participation of this molecule causing the death of cells in the 3t3 line, this agrees with the literature, since it induces apoptosis in fibroblasts (Jin et al, 2019), as well as Bisdemethoxyrcurcumin has been shown to induce apoptosis, and inhibit the proliferation of cancer cells (Liu et al, 2011;Li et al, 2013).There are few reports in the literature of in vitro genotoxicity caused by Moringa oleifera extracts (Alkan et al, 2022), according to these results, Moringa extracts can cause DNA damage causing fragmentation, which is related to the mechanism of apoptosis already reported. In this study, it was found that ethanolic extracts cause DNA fragmentation, and this damage is related to the concentration of the extract.…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, the presence of Bisdemethoxyrcurcumin exclusively in the ethanolic fraction suggests the participation of this molecule causing the death of cells in the 3t3 line, this agrees with the literature, since it induces apoptosis in fibroblasts (Jin et al, 2019), as well as Bisdemethoxyrcurcumin has been shown to induce apoptosis, and inhibit the proliferation of cancer cells (Liu et al, 2011;Li et al, 2013).There are few reports in the literature of in vitro genotoxicity caused by Moringa oleifera extracts (Alkan et al, 2022), according to these results, Moringa extracts can cause DNA damage causing fragmentation, which is related to the mechanism of apoptosis already reported. In this study, it was found that ethanolic extracts cause DNA fragmentation, and this damage is related to the concentration of the extract.…”
Section: Discussionsupporting
confidence: 86%
“…By targeting drug delivery directly to cancer cells, their better bioavailability can improve the effectiveness of antitumor therapy and minimize side effects [ 47 ]. The mechanisms of action of silver nanoparticles and their conjugates with antitumor agents include the production of ROS and oxidative stress, DNA damage, cell cycle arrest, and the induction of tumor cell death by apoptosis, as well as by nonapoptotic types of cell death [ 48 , 49 , 50 ].…”
Section: The Potential Of Agnps In Nano-oncologymentioning
confidence: 99%
“…Only a few in vivo studies have been reported using the comet assay and/or D. melanogaster as model organism to determine the genotoxicity of commercial AgNPs or photosynthesized AgNPs. [54][55][56] Previously, the genotoxic effects of commercial AgNPs and silver nitrate in D. melanogaster hemocytes have been determined by comet assay. 32 In D. melanogaster wings imaginal disks AgNPs were also induced signicant levels of genotoxic damage as determined by the wing-spot assay.…”
Section: Evaluation Of Dna Damagementioning
confidence: 99%